2016
DOI: 10.1016/j.celrep.2016.05.084
|View full text |Cite
|
Sign up to set email alerts
|

A c-Myc/miR17-92/Pten Axis Controls PI3K-Mediated Positive and Negative Selection in B Cell Development and Reconstitutes CD19 Deficiency

Abstract: PI3K activity determines positive and negative selection of B cells, a key process for immune tolerance and B cell maturation. Activation of PI3K is balanced by phosphatase and tensin homolog (Pten), the PI3K's main antagonistic phosphatase. Yet, the extent of feedback regulation between PI3K activity and Pten expression during B cell development is unclear. Here, we show that PI3K control of this process is achieved post-transcriptionally by an axis composed of a transcription factor (c-Myc), a microRNA (miR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 68 publications
(117 reference statements)
6
55
0
Order By: Relevance
“…These are B-cell-intrinsic mechanisms and are known to be controlled by B-cell antigen receptor signalling thresholds and regulators of the phosphoinositide 3-kinase pathway [19–21]. Recently, the miR-17–92 family of miRNA has been shown to regulate central B-cell tolerance by targeting phosphatase and tensin homolog [20, 22]. Additional removal of autoreactive B cells occurs by selection mechanisms in the periphery, which are less clear but can involve impaired survival and anergy [23].…”
Section: Breaking Immune Tolerance and The Development Of Autoimmunitymentioning
confidence: 99%
“…These are B-cell-intrinsic mechanisms and are known to be controlled by B-cell antigen receptor signalling thresholds and regulators of the phosphoinositide 3-kinase pathway [19–21]. Recently, the miR-17–92 family of miRNA has been shown to regulate central B-cell tolerance by targeting phosphatase and tensin homolog [20, 22]. Additional removal of autoreactive B cells occurs by selection mechanisms in the periphery, which are less clear but can involve impaired survival and anergy [23].…”
Section: Breaking Immune Tolerance and The Development Of Autoimmunitymentioning
confidence: 99%
“…Inducible ablation of Dicer (and thus all miRNAs) in transitional B cells has been documented to lead to a reduction of PI3K signaling and apoptosis in these cells [40]; these defects could be rescued by reducing levels of Pten in vivo, in mice [40]. Specifically, by using CD19-deficient mice where PI3K signaling is diminished [41], the authors showed that decreased levels of c-Myc (known to be regulated by PI3K), led to reduced miR-19 expression and increased Pten mRNA and protein levels [40]. This result suggests a regulatory loop where BCR signaling via PI3K induces c-Myc expression, in turn activating miR-17~92 expression, which presumably contributes to Pten-mediated inhibition of PI3K, and thus contributing to the regulation of central tolerance [40].…”
Section: Mirnas In Central Tolerancementioning
confidence: 99%
“…Specifically, by using CD19-deficient mice where PI3K signaling is diminished [41], the authors showed that decreased levels of c-Myc (known to be regulated by PI3K), led to reduced miR-19 expression and increased Pten mRNA and protein levels [40]. This result suggests a regulatory loop where BCR signaling via PI3K induces c-Myc expression, in turn activating miR-17~92 expression, which presumably contributes to Pten-mediated inhibition of PI3K, and thus contributing to the regulation of central tolerance [40]. Taken together, these results underscore the role of the miR-17~92 cluster in the regulation of B cell central tolerance and the fundamental role this cluster plays in maintaining immune homeostasis.…”
Section: Mirnas In Central Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Gadd45α was reported to induce translocation of Bim to mitochondria where Bim inhibits apoptosis 59 , and its defect causes lupus-like disease 60 . miR17-92 also regulates PTEN 57, 61 . Thus, Bim and the PI-3K pathway regulated by PTEN play a crucial role in microRNA-mediated regulation of B-cell tolerance.…”
Section: Regulation Of Central Tolerance and Clonal Anergy By Apoptosmentioning
confidence: 99%